Speed of call delivery is related to context and caller identity in Campbell’s monkey males - Lemasson, Alban; Ouattara, Karim; Bouchet, Hélène; Zuberbühler, Klaus (My University, 2010)
Call rate can be a salient feature in animal communication. Depending on the species, different psychological variables appear to influence call rates but the exact nature of these relationships remains poorly explored. Here, we demonstrate for free-ranging Campbell's monkeys that the call rates of four different alarm series (termed H, K, K+, and B series) vary systematically as a function of context, associated behaviour, and identity of the caller. K+ series were given more rapidly to predation than non- predation events, K+ and K series more rapidly to visual than auditory predator detection, and H series more rapidly while counterattacking an eagle than staying put. Finally, there were individual differences in B series, suggesting that call rate potentially provides listeners with cues about the caller's anti-predator behaviour, event type experienced, and his identity.
Keywords: Prosody; Predation; Cercopithecus; Loud call; Tempo; Semantic